White Matter Abnormalities in Patients With Typhoon-Related Posttraumatic Stress Disorder - Chen, Hui Juan; Qi, Rongfeng; Ke, Jun; Qiu, Jie; Xu, Qiang; Zhong, Yuan; Lu, Guang Ming; Chen, Feng (Frontiers in Human Neuroscience, 2021)
Post-traumatic stress disorder (PTSD) patients might have white matter abnormalities. However, little is known about white matter changes after exposing a specific traumatic event. The purpose of our study was to explore the abnormalities of diffusion in cerebral white matter and its relationship with the clinical symptoms in patients with PTSD by using diffusion tensor imaging (DTI). Diffusion weighted imaging of the cerebrum was performed in typhoon survivors with (n = 27) and without PTSD (n = 33) and healthy controls (HC) (n = 30). Differences in fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) were calculated among groups using voxel-based analysis of the DTI data. Correlations between diffusion indices and clinical symptoms in PTSD patients were also assessed. Both PTSD patients and trauma exposed control (TEC) group showed increased FA in the anterior limb of internal capsule, forceps of corpus callosum, corona radiata relative to the HC group. Additionally, there was a negative correlation between FA values in the white matter and the clinical symptoms. Trauma exposure may result in disruption of cerebral white matter in individuals with or without PTSD, particularly in the frontal fibers. Aberrant white matter alterations may be associated with PTSD symptom severity.